PEMBUATAN ARANG AKTIF DARI BIOMAS UNTUK PEMURNI MINYAK KELAPA - Gustan Pari; Hartoyo Hartoyo (Jurnal Penelitian Hasil Hutan, 1989)
Steam  activation   char of  wood,  bamboo,  and coconut shell  to produce  activated  charcoal were carried out  in a labora- tory  scale electric  heated  retort.The  treatment   conditions   applied  for  activation   were  temperature   of  700°C,  steam  flow  rate  of  30 g/minute  and reaction  time  15 minutes.   The  activated  charcoals produced   from   the  experiment   were  respectively   used  for refining  the samples  of  low grade commercial   coconut oil obtained   from   the  market.The  results  showed   that  all of  the  activated   charcoal  produced   can  increase   the  quality   of  coconut  oil  to  meet requirements   of  the  Indonesian   Industrial   Standard  (Sll).